2016
DOI: 10.1242/dev.137844
|View full text |Cite
|
Sign up to set email alerts
|

miR-219 regulates neural progenitors by dampening apical Par protein-dependent Hedgehog signaling

Abstract: The transition of dividing neuroepithelial progenitors to differentiated neurons and glia is essential for the formation of a functional nervous system. Sonic hedgehog (Shh) is a mitogen for spinal cord progenitors, but how cells become insensitive to the proliferative effects of Shh is not well understood. Because Shh reception occurs at primary cilia, which are positioned within the apical membrane of neuroepithelial progenitors, we hypothesized that loss of apical characteristics reduces the Shh signaling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…Its downregulation is significant as it leads to the downregulation of the genes in RNA processing . In addition, the downregulation of miR‐219 is consistent with a single brief re‐exposure to the context that could inhibit the signaling activity and promote memory reconsolidation . It has been reported that miR‐219 participates in the NMDAR signaling by regulating the expression of pathway genes .…”
Section: Discussionsupporting
confidence: 56%
“…Its downregulation is significant as it leads to the downregulation of the genes in RNA processing . In addition, the downregulation of miR‐219 is consistent with a single brief re‐exposure to the context that could inhibit the signaling activity and promote memory reconsolidation . It has been reported that miR‐219 participates in the NMDAR signaling by regulating the expression of pathway genes .…”
Section: Discussionsupporting
confidence: 56%
“…Another miRNA that also exhibited similar characteristics in LGG was miR-219 and, intriguingly, this miRNA has been implicated in neural differentiation processes (52). We were also able to identify additional miRNAs that have almost unique expression in some tissues, like the liver-specific arms of miR-122 (53).…”
Section: Discussionmentioning
confidence: 61%
“…A recent study suggested that overexpression of miR‐219 in neural stem cells robustly inhibits cell proliferation and induces neuronal differentiation (Murai et al ). Another recent report also described that miR‐219 appears to decrease progenitor cell sensitivity to Shh signaling, thereby driving neural progenitors towards differentiation (Hudish et al ). Recently, miR‐219a‐5p was reported to play a crucial role in schizophrenia, osteosarcoma, and age‐related bone loss (Hass et al ; Li et al ; Aquino‐Martinez et al ).…”
Section: Discussionmentioning
confidence: 97%